Injury Epidemiology and Risk Factors in Female Kabaddi Athletes: Insights from Event PON XXI 2024 for Enhanced Prevention and Management - Ahmad Al Munawar; Şenay Şen; Filli Azadi (Inspiree)
The  purpose  of  the study. This research examines injury patterns, prevalence, and management in female Kabaddi athletes from North Sumatra during the PON XXI 2024 competition, addressing a gap in sports medicine regarding the physiological challenges faced by women in this contact sport. Kabaddi's lack of research on female athletes contributes to a significant deficit in understanding its physiological impact on women.